FUNGSI DINAS KESEHATAN KOTA PEKANBARU DALAM MENGURANGI ANGKA KEMATIAN IBU DAN ANAK DI KOTA PEKANBARU PERIODE 2018-2019 - Adib Murtadho Aslam; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT Improving maternal health has become the main priority of the government, various efforts have been made by the government to improve maternal health. The progress of a country, in essence, is inseparable from the quality of maternal and child health, because from a good mother's health, the next generation of responsible nations will be born. However, until now it is still marked by the vulnerable health status of mothers and children, especially in the most vulnerable groups, namely pregnant, maternity and postpartum women, as well as newborns, which causes the still high Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). Pekanbaru City is the capital of Riau Province with the highest MMR and IMR in Riau Province, while from 2015 - 2018 cases continued to increase and fell in 2019, although not significantly. Based on these problems, the formulation of the research problem is: